A hydrophobic deep eutectic solvent‐based vortex‐assisted dispersive liquid–liquid microextraction combined with HPLC for the determination of nitrite in water and biological samples. Issue 2 (19th November 2018) - Zhang, Kaige; Li, Shuangying; Liu, Chuang; Wang, Qi; Wang, Yunhe; Fan, Jing
Abstract: In recent years, hydrophobic deep eutectic solvents as new generation of green solvents have attracted wide attention in liquid microextraction technique. In this article, four hydrophobic deep eutectic solvents composed of trioctylmethylammonium chloride and oleic acid were designed and prepared firstly. Combined with high‐performance liquid chromatography, these deep eutectic solvents were used as an extraction solvent in vortex‐assisted dispersive liquid–liquid microextraction for the selective enrichment and indirect determination of trace nitrite from real water and biological samples. This method is based on the diazotization‐coupling reaction of nitrite with p ‐nitroaniline and diphenylamine in acidic water, and then the nitrite is quantified indirectly by measuring the obtained azo compounds. Some factors influencing the extraction efficiency, including the reaction and extraction conditions, were investigated. Under the optimized conditions, the method has a linear range of 1–300 μg/L with a correlation coefficient of 0.9924, limit of detection of 0.2 μg/L, limit of quantitation of 1 μg/L, intraday and interday relative standard deviations of 4.0 and 6.0%. This method was successfully applied in determination of nitrite from three environmental water and two biological samples with the recovery in the range of 90.5–115.2%. In addition, these results were well agreement with those obtained by the conventional Griess method.